CASE OF PRIMARY AMYLOIDOSIS WITH INVOLVEMENT OF THE HEART AND PERICARDIUM IN CARDIOLOGY PRACTICE - I. V. Demko; L. I. Pelinovskaya; V. A. Mosina; A. Y. Kraposhina; N. V. Gordeeva; I. A. Solovyova; A. E. Ryazanov (Российский кардиологический журнал)
In the article, a case presented of primary amyloidosis of the heart and pericardium, with severe resistant heart failure. That kind of case witnesses that diagnostics and management of patients with this disease, is a complicated issue in cardiology practice. That is related to its rarity, absence of key simptoms in clinical practice and delayed diagnostics with lack of expected efficacy of modern treatment.